2022
DOI: 10.1002/anie.202212637
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Enzyme Substrate Scope Complementarity for Promiscuous Cascade Synthesis of 1,2‐Amino Alcohols

Abstract: Biocatalytic cascades are uniquely powerful for the efficient, asymmetric synthesis of bioactive compounds. However, high substrate specificity can hinder the scope of biocatalytic cascades because the constituent enzymes may have non‐complementary activity. In this study, we implemented a substrate multiplexed screening (SUMS) based directed evolution approach to improve the substrate scope overlap between a transaldolase (ObiH) and a decarboxylase for the production of chiral 1,2‐amino alcohols. To generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…This substrate multiplexed screening (SUMS) approach offers several distinct advantages compared to single-substrate measurements. 61,62 In SUMS unimolecular transformations, the ratio of the products is directly proportional to the ratio of the catalytic efficiencies. For bimolecular reactions, however, complex kinetic phenomena can break the pseudo-first-order relationship between catalytic efficiency and specificity.…”
Section: Resultsmentioning
confidence: 99%
“…This substrate multiplexed screening (SUMS) approach offers several distinct advantages compared to single-substrate measurements. 61,62 In SUMS unimolecular transformations, the ratio of the products is directly proportional to the ratio of the catalytic efficiencies. For bimolecular reactions, however, complex kinetic phenomena can break the pseudo-first-order relationship between catalytic efficiency and specificity.…”
Section: Resultsmentioning
confidence: 99%
“…This substrate multiplexed screening (SUMS) approach offers several distinct advantages compared to single substrate measurements. 34,35 Comparison of relative rates of product formation from single-substrate reactions provides only indirect information about specificity. By assaying multiple substrates in competition, SUMS gives direct information on the ability of an enzyme to discriminate between two or more substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Two examples of epoxides 1 were also converted via this sequence of isomerization, CÀ C bond formation and decarboxylation to produce enantiopure benzylic 1,2-amino alcohols 22 a and 22 b in 27 to 33 % isolated yields (Scheme 5b). [37] The same group also demonstrated that aldehydes 2 generated in situ by SOI from 1 can be intercepted by another enzyme that catalyzes a decarboxylative aldol addition (UstD v2.0 ), thus producing γ-hydroxy amino acids 23 a and 23 b, albeit with low diastereoselectivity of 5 : 2 to 7 : 2 (Scheme 5c). [34] Cascades Involving SOI-Catalyzed Epoxide Isomerization to Synthesize Natural Chemicals from Renewable Substrates SOI has been incorporated as a key enzyme in cascade biotransformations to convert renewable bio-based substrates into high-value products.…”
Section: Cascades Involving Soi-catalyzed Epoxide Isomerization and E...mentioning
confidence: 98%
“…Racemic 6 a was converted by 0.1 %w/v whole cells harbouring SOI to generate 4 a in situ, which was subsequently converted by purified ObiH and Rgn TDC NMY to produce benzylic 1,2‐amino alcohol 21 a as a single diastereomer in 61 % analytical yield and 39 % isolated yield. Two examples of epoxides 1 were also converted via this sequence of isomerization, C−C bond formation and decarboxylation to produce enantiopure benzylic 1,2‐amino alcohols 22 a and 22 b in 27 to 33 % isolated yields (Scheme 5b) [37] . The same group also demonstrated that aldehydes 2 generated in situ by SOI from 1 can be intercepted by another enzyme that catalyzes a decarboxylative aldol addition (UstD v2.0 ), thus producing γ ‐hydroxy amino acids 23 a and 23 b , albeit with low diastereoselectivity of 5 : 2 to 7 : 2 (Scheme 5c) [34] …”
Section: Cascades Involving Soi‐catalyzed Epoxide Isomerization and E...mentioning
confidence: 99%